Aggregating web–based ideation platforms. (18th June 2012) - Finzen, Jan; Kintz, Maximilien; Kaufmann, Stefan
Today, lots of online communities co–exist where users suggest and discuss ideas and problems. However, the diversity of such idea networks and the high launch rate of new platforms make it hard to keep track of the current idea community landscape. This article presents an approach to integrate arbitrary online ideation platforms that allow users to publicly utter and discuss new ideas or provide solutions to previously announced problems. We introduce our prototypical implementation of the approach that provides a single point of access for innovation managers, problem solvers and solution seekers.